Avifauna Composition and its habitat in the Paya Indah Freshwater Wetland Ecosystem, Malaysia - Rajpar, Muhammad Nawaz (2010)
Birds are the most conspicuous and significant components of freshwater wetland ecosystem and their presence or absence may indicate the ecological conditions of the wetland area. The objectives of this study were to determine species composition, diversity, density, feeding guilds and correlation of birds with microclimate and microhabitat conditions. The study was conducted using distance sampling point count and mist-netting methods at Paya Indah Wetland Reserve, Peninsular Malaysia. A total of 122 bird species and 42 families (including 12 opportunistic observations) were recorded during 15 consecutive months of the study period, from November 2007 to January 2009. The point count method detected 100 species of birds (25 waterbird species and 75 terrestrial bird species) belonging to 38 families. Meanwhile, the mist-netting method captured 65 bird species (18 waterbird species and 47 terrestrial bird iv species) belonging to 33 families. The bird density of the wetland reserve was 83.92 ± 4.53 birds/ha which ranged from 75.40 – 93.41 birds/ha (95% confidence interval). The density of the terrestrial birds was higher (70.26 ± 4.48 birds/ha) than the waterbirds (13.09 ± 1.78 birds/ha). Furthermore, the resident birds showed the highest bird density (72.17 ± 3.77 birds/ha) compared to the resident and migratory birds (8.86 ± 0.86 birds/ha), migratory birds (3.77 ± 0.50 birds/ha) and vagrant birds (0.13 ± 0.08 birds/ha). In addition, the highest density was recorded in Marsh Swamp (136.55 ± 21.21 birds/ha) as compared to Lotus Swamp (95.42 ± 6.96 birds/ha), Shrub Patches (86.47 ±8.36 birds/ha), Dryland (75.22 ± 7.09 birds/ha) and Open Water Body (70.40 ± 11.14 birds/ha). White-throated Kingfisher (Halcyon smyrensis; 66 captures; 32.84%) for waterbirds and Yellow-vented Bulbul (Pycnonotus goiavier; 379 captures; 29.68%) for terrestrial birds were the most abundant species based on mist-netting captured. In addition, eight waterbird species (0.49% each) and nine terrestrial bird species were the rarest species (0.08% each). The Pycnonotidae was the most dominant family (385 individuals; 26.05%) whereas the Phasianidae, Coraciidae and Muscicapidae were the rarest families with only one individual captured each (0.07%) based on mist-netting. Meanwhile, the point count results showed that Carnivore/Piscivore/Insectivore was the most dominant guilds (1.48 ± 0.13 birds/ha) and Insectivore was the rarest guild (0.42 ± 0.27 birds/ha) for waterbirds. In addition, the Granivore was most abundant guild (2.81 ± 0.38 birds/ha) while the Carnivore was the rarest guild (0.46 ± 0.22 birds/ha) for terrestrial birds. Furthermore, the mist-netting method indicated that Carnivore/Piscivore/Insectivore was the most dominant guilds (81.89%), while Omnivore was the rarest guild (18.41%) for waterbirds. The Frugivore/Insectivore was the most abundant guild (38.06%) and the Carnivore was the rarest guild (0.55%) for terrestrial birds. Both the point count and the mist-netting methods showed that terrestrial birds have higher species diversities, i.e. Shannon‟s index (point count; N1 = 20.83 and mist-netting; N1 = 14.97), species richness, i.e. Margalef‟s index (point count; R1 = 7.97 and mist-netting; R1 = 6.43) and species evenness, i.e. McIntosh‟s index (point count; E = 0.73 and mist-netting; E = 0.66) as compared to waterbirds, i.e. Shannon‟s index (point count; N1 = 9.56 and mist-netting; N1 = 7.23) and species richness, i.e. Margalef‟s index (point count; R1 = 2.99 and mist-netting; R1 = 3.21) and species evenness, i.e. McIntosh‟s index (point count; E = 0.62 and mist-netting; E = 0.60). Moreover, the point count method indicated that Marsh Swamp had a higher species diversity (Shannon index; N1 = 27.16), species richness (Margalef‟s index; R1 = 9.52) and species evenness (Pielou‟s J Evenness; E = 0.71) as compared to Lotus Swamp, Open Water Body, Dryland and Shrub Patches. The Canonical Correspondence Analysis revealed that the microhabitat characteristics such as vegetation composition (i.e. emergent and submerged vegetations, grasses, shrubs and trees), vegetation structures (tree diameter and height), vegetation layers (ground vegetation, shrubs and tree layers), microclimate variables (temperature, relative humidity and light intensity) and water level were the key factors that influenced the distribution, diversity and density of the wetland avian species. This study also revealed that the wetland bird species have adapted a fairly unique set of microhabitat and microclimate conditions. Therefore, this study showed that the distance sampling point count method was more efficient and produced better results than the mist-netting method particularly in terms of species composition, diversity and feeding guilds. Moreover, mist-netting should be applied as a supplement method to the point count in obtaining accurate estimates because mist-netting is more effective to record small, highly cryptic and shy bird species with secretive behaviour. The results also indicated that marsh swamp and open water body have “Class II A” water quality, while lotus swamp has “Class III” water quality. The results of this study clearly indicated that Paya Indah Wetland Reserve is a highly important area in providing diverse food resources, shelter, nesting and roosting sites for a wide range of bird species, particularly for the waterbird and terrestrial species. Therefore, the wetland area should be protected and declared as another Ramsar site for the country.